Practicality of using visual analysis in researching e -learning affordances - Jamian, Magdalina; Ab. Jalil, Habibah; Krauss, Steven Eric; Ismail, Ismi Arif; Hassan, Aminuddin; Abd Rahman, Fadzilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
One of the struggles in researching e-learning is to capture the setting. This paper aims to illuminate the complexity of conducting research that is meant to understand learning settings, particularly those with eLearning integrations. In an ICT setting, affordances can be defined as the facts about an e-learning environment (Wells, 2002) and how those facts are interpreted by the user interacting with that environment (Norman, 1988; 1990). It is important to study affordances in e-learning in order to identify the environmental conduciveness that affects the utilization of ICT tools. Affordances of ICT facilities provided to students in one Malaysian public higher education institution is the main concern of this paper. Visual analysis was conducted to analyze pictorial data of the e-learning environment. This methodology is typically used to capture settings that are difficult to do so using narrative textual forms by making use of photography to record particular subjects at a particular moment (Harper, 2003). Suggested key terms are proposed as a guideline for analyzing the pictorial data. Affordances of the e-learning environment were analyzed through the researchers' interpretations of the tools, setting and utilization evidenced in the visual records and descriptions of the records. The facilities, condition of the facilities and the environment were captured and examined for demographic and cultural patterns. In so doing, this conceptual paper offers a unique methodological perspective in researching the affordances of ICT in a Malaysian higher education institution.